Comic book cartographies: a cartocentred reading of City of Glass, the graphic novel. (January 2017) - Peterle, Giada
This article responds to the call for a deeper theoretical and methodological exchange between the disciplines involved in geohumanities research and proposes comic books as an environment for inter disciplinary, geo/cartographical and literary critical research practice. The analysis considers the emerging field of 'comic book geographies' and suggests a further opening to 'comic book cartographies'. Hence, by referring to the 'spatiocentred' approaches emerging in literary theory and criticism, I propose a 'geocritical' and 'cartocentred' reading of comics to explore the 'cartographies of the comic book'. I individuate the peculiar map-like features of comics' spatial grammar to interpret the comic book as both a cartographer and a map. Moreover, taking into account the recent shift in cartographic theory towards an 'emergent cartography', I propose an 'ontogenetic' understanding of comics as maps. Through both their representational and non-representational map-like features, comics are intended 'as always mappings', providing the author/reader with a truly mapping experience. The analysis of the exemplary case study of City of Glass, the graphic novel transposition of Auster's novel by Paul Karasik and David Mazzucchelli, counts as a first attempt to propose a 'cartocentred' reading of the cartographies inserted within and emerging from a comic book. This article suggests that a 'cartocritical' reading of comics could provide comic studies, cultural geography and literary theory with new insights, as well as cartographic theory with an unexplored laboratory to keep on 'rethinking maps' from an 'emergent' perspective.